PROFIL KOMUNIKASI MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI KECERDASAN LINGUISTIK - Nur Laili Mutmainah; Sardulo Gembong; Davi Apriandi (IKIP PGRI MADIUN, 2016)
This study aims to determine the mathematical communication profile secondary school students in solving mathematical problems regarding linguistic intelligence. Determination of the subjects in this study is based on linguistic intelligence test scores eighth-grade students of SMP Negeri 1 A western numbering 35 students. Based on the results of the linguistic intelligence test scores have six subjects were categorized into three categories, namely two subjects with high linguistic intelligence, two subjects with moderate linguistic intelligence, and two subjects with low linguistic intelligence. This type of research is qualitative descriptive study. Data collection techniques in this study were obtained based on the results of tests, interviews, and documentation. Technique authenticity of data is done by a triangulation method. Data analysis was performed with data reduction, data presentation and verification of data. The conclusion of this study were (1) students with a high in linguistic intelligence has a tendency to comply with all aspects of mathematical communication, (2) students with linguistic intelligence medium category have a tendency to meet aspects mathematical communication, but the aspect of using representation thoroughly to express the concept of mathematics and solutions and strategies stated settlement of a problem are small, (3) students with linguistic intelligence little category have a tendency mathematical communication is low, it can be seen in every aspect of mathematical communication pertained mostly low category.